The Impact of Digitalization on Regional Macro Development Indicators - Fajriani, Khoirina; Rahmayana , Lintang (Journal of Indonesian Rural and Regional Government, 2025)
In the era of Internet of Things, digitalization has become one of the key factors driving the progress of regions. According to various studies, digitalization brings positive impacts across various sectors, including social, economic, labor, and others. The topic of how digitalization affects regional development has been extensively discussed, but most studies focus primarily on the effects of digitalization in developed countries. On the other side, research regarding the relationship between digitalization and macro-level regional development achievements is still limited in developing countries. Therefore, this study seeks to examine the impact of digital transformation on macro-level development outcomes in developing countries, particularly focusing on Indonesia. This study uses a quantitative approach with regression methods. The data used is macro-level data from all provinces in Indonesia, specifically data related to variables concerning digitalization and regional development achievements. The findings show that digitalization has a significant positive impact on the quality of life and the economic contributions of regions.